Coulomb Functions - 33.19 Power-Series Expansions in

From testwiki
Revision as of 17:58, 25 May 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
33.19.E4 γ k - γ k - 1 + 1 4 ( k - 1 ) ( k - 2 - 2 ) ϵ γ k - 2 = 0 subscript 𝛾 𝑘 subscript 𝛾 𝑘 1 1 4 𝑘 1 𝑘 2 2 italic-ϵ subscript 𝛾 𝑘 2 0 {\displaystyle{\displaystyle\gamma_{k}-\gamma_{k-1}+\tfrac{1}{4}(k-1)(k-2\ell-% 2)\epsilon\gamma_{k-2}=0}}
\gamma_{k}-\gamma_{k-1}+\tfrac{1}{4}(k-1)(k-2\ell-2)\epsilon\gamma_{k-2} = 0

gamma[k]- gamma[k - 1]+(1)/(4)*(k - 1)*(k - 2*ell - 2)*epsilon*gamma[k - 2] = 0
Subscript[\[Gamma], k]- Subscript[\[Gamma], k - 1]+Divide[1,4]*(k - 1)*(k - 2*\[ScriptL]- 2)*\[Epsilon]*Subscript[\[Gamma], k - 2] == 0
Skipped - no semantic math Skipped - no semantic math - -
33.19.E6 k ( k + 2 + 1 ) δ k + 2 δ k - 1 + ϵ δ k - 2 + 2 ( 2 k + 2 + 1 ) A ( ϵ , ) α k = 0 𝑘 𝑘 2 1 subscript 𝛿 𝑘 2 subscript 𝛿 𝑘 1 italic-ϵ subscript 𝛿 𝑘 2 2 2 𝑘 2 1 𝐴 italic-ϵ subscript 𝛼 𝑘 0 {\displaystyle{\displaystyle k(k+2\ell+1)\delta_{k}+2\delta_{k-1}+\epsilon% \delta_{k-2}+2(2k+2\ell+1)A(\epsilon,\ell)\alpha_{k}=0}}
k(k+2\ell+1)\delta_{k}+2\delta_{k-1}+\epsilon\delta_{k-2}+2(2k+2\ell+1)A(\epsilon,\ell)\alpha_{k} = 0

k*(k + 2*ell + 1)*delta[k]+ 2*delta[k - 1]+ epsilon*delta[k - 2]+ 2*(2*k + 2*ell + 1)*(product(1 + epsilon*(k)^(2), k = 0..ell))*alpha[k] = 0
k*(k + 2*\[ScriptL]+ 1)*Subscript[\[Delta], k]+ 2*Subscript[\[Delta], k - 1]+ \[Epsilon]*Subscript[\[Delta], k - 2]+ 2*(2*k + 2*\[ScriptL]+ 1)*(Product[1 + \[Epsilon]*(k)^(2), {k, 0, \[ScriptL]}, GenerateConditions->None])*Subscript[\[Alpha], k] == 0
Skipped - no semantic math Skipped - no semantic math - -
33.19.E7 β k - β k - 1 + 1 4 ( k - 1 ) ( k - 2 - 2 ) ϵ β k - 2 + 1 2 ( k - 1 ) ϵ γ k - 2 = 0 subscript 𝛽 𝑘 subscript 𝛽 𝑘 1 1 4 𝑘 1 𝑘 2 2 italic-ϵ subscript 𝛽 𝑘 2 1 2 𝑘 1 italic-ϵ subscript 𝛾 𝑘 2 0 {\displaystyle{\displaystyle\beta_{k}-\beta_{k-1}+\tfrac{1}{4}(k-1)(k-2\ell-2)% \epsilon\beta_{k-2}+\tfrac{1}{2}(k-1)\epsilon\gamma_{k-2}=0}}
\beta_{k}-\beta_{k-1}+\tfrac{1}{4}(k-1)(k-2\ell-2)\epsilon\beta_{k-2}+\tfrac{1}{2}(k-1)\epsilon\gamma_{k-2} = 0

beta[k]- beta[k - 1]+(1)/(4)*(k - 1)*(k - 2*ell - 2)*epsilon*beta[k - 2]+(1)/(2)*(k - 1)*epsilon*gamma[k - 2] = 0
Subscript[\[Beta], k]- Subscript[\[Beta], k - 1]+Divide[1,4]*(k - 1)*(k - 2*\[ScriptL]- 2)*\[Epsilon]*Subscript[\[Beta], k - 2]+Divide[1,2]*(k - 1)*\[Epsilon]*Subscript[\[Gamma], k - 2] == 0
Skipped - no semantic math Skipped - no semantic math - -